Tissue Trafficking Kinetics of Rhesus Macaque Natural Killer Cells Measured by Serial Intravascular Staining - Mortlock, Ryland D.; Wu, Chuanfeng; Potter, E. Lake; Abraham, Diana M.; Allan, David S. J.; Hong, So Gun; Roederer, Mario; Dunbar, Cynthia E. (Frontiers in Immunology, 2022)
The in vivo tissue distribution and trafficking patterns of natural killer (NK) cells remain understudied. Animal models can help bridge the gap, and rhesus macaque (RM) primates faithfully recapitulate key elements of human NK cell biology. Here, we profiled the tissue distribution and localization patterns of three NK cell subsets across various RM tissues. We utilized serial intravascular staining (SIVS) to investigate the tissue trafficking kinetics at steady state and during recovery from CD16 depletion. We found that at steady state, CD16+ NK cells were selectively retained in the vasculature while CD56+ NK cells had a shorter residence time in peripheral blood. We also found that different subsets of NK cells had distinct trafficking kinetics to and from the lymph node as well as other lymphoid and non-lymphoid tissues. Lastly, we found that following administration of CD16-depleting antibody, CD16+ NK cells and their putative precursors retained a high proportion of continuously circulating cells, suggesting that regeneration of the CD16 NK compartment may take place in peripheral blood or the perivascular compartments of tissues.